Assessment of phytotoxic potential and pathogenic bacteria removal from secondary effluents during ozonation and UV/H2O2 - Sommaggio, Lais Roberta Deroldo [UNESP]; Oliveira, Flávio A.; Malvestiti, Jacqueline Aparecida; Mazzeo, Dânia Elisa Christofoletti; Levy, Carlos Emílio; Dantas, Renato Falcão; Marin-Morales, Maria Aparecida [UNESP] (Elsevier, 2022)
Wastewater reuse is an important strategy for water resource management. For this reason, the disinfection process must be appropriated, eliminating pathogenic microorganisms. Ozonation (O3) and UV/H2O2 treatments can be used for effluent disinfection, but few studies just address the Escherichia coli quantification. In this study, secondary effluents from two wastewater treatment plants with different characteristics were exposed to O3 (5 and 10 mg L−1) or UV/H2O2 (H2O2: 90 mg L−1) treatments and evaluated by BD Phoenix ™ 100 (Becton Dickinson, USA) and MALDI-TOF for the characterization of the indigenous microorganisms in the effluents, before and after treatments. Additionally, all the samples were tested for phytotoxicity by Lactuca sativa bioassay. The results showed that the highest ozone dose and the UV/H2O2 treatment were effective in removing E. coli. UV/H2O2 was more efficient as it eliminated most of the microorganisms. Acinetobacter sp., Aeromonas and Pseudomonas were still found after O3 treatment. Bacillus sp. was found after O3 and UV/H2O2 treatments. The results with L. sativa showed inhibition of root growth for all dry period (low rainfall) samples of one of the WWTP, due to the high concentration of the phytotoxicity compounds. For environmental and human health safety, treated effluents should be evaluated for their toxic and pathogenic potential before being released into the environment. Pathogens evaluation on treated effluents should cover a wider range of pathogenic microorganisms than those routinely required by legislation.
Keywords: Advanced oxidation processes; Bacillus sp; Disinfection; Lactuca sativa; Wastewater; Water management